Non-classical HLA-E restricted CMV 15-mer peptides are recognized by adaptive NK cells and induce memory responses - Almazán Nerea Martín; Sala Benedetta Maria; Sandalova Tatyana; Sun Yizhe; Resink Tom; Cichocki Frank; Söderberg-Nauclér Cecilia; Miller Jeffrey S.; Achour Adnane; Sarhan Dhifaf (Frontiers Research Foundation, 2025)
Introduction: Human cytomegalovirus (HCMV) reactivation causes complications in immunocompromised patients after hematopoietic stem cell transplantation (HSCT), significantly increasing morbidity and mortality. Adaptive Natural Killer (aNK) cells undergo a persistent reconfiguration in response to HCMV reactivation; however, the exact role of aNK cell memory in HCMV surveillance remains elusive.
Methods: We employed mass spectrometry and computational prediction approaches to identify HLA-E-restricted HCMV peptides that can elucidate aNK cell responses. We also used the K562 cell line transfected with HLA-E0*0103 for specific peptide binding and blocking assays. Subsequently, NK cells were cocultured with dendritic cells (DCs) loaded with each of the identified peptides to examine aNK and conventional (c)NK cell responses.
Results: Here, we discovered three unconventional HLA-E-restricted 15-mer peptides (SEVENVSVNVHNPTG, TSGSDSDEELVTTER, and DSDEELVTTERKTPR) derived from the HCMV pp65-protein that elicit aNK cell memory responses restricted to HCMV. aNK cells displayed memory responses towards HMCV-infected cells and HCMV-seropositive individuals when primed by DCs loaded with each of these peptides and predicted 9-mer versions. Blocking the interaction between HLA-E and the activation NKG2C receptor but not the inhibitory NKG2A receptor abolished these specific recall responses. Interestingly, compared to the HLA-E complex with the leader peptide VMAPRTLIL, HLA-E complexes formed with each of the three identified peptides significantly changed the surface electrostatic potential to highly negative. Furthermore, these peptides do not comprise the classical HLA-E-restriction motifs.
Discussion: These findings suggest a differential binding to NKG2C compared to HLA-E complexes with classical leader peptides that may result in the specific activation of aNK cells. We then designed six nonameric peptides based on the three discovered peptides that could elicit aNK cell memory responses to HCMV necessary for therapeutic inventions. The results provide novel insights into HLA-E-mediated signaling networks that mediate aNK cell recall responses and maximize their reactivity.